Effect of race on the measurement of angiogenic factors for prediction and diagnosis of pre‐eclampsia. (17th October 2022) - Wright, Alan; von Dadelszen, Peter; Magee, Laura A.; Syngelaki, Argyro; Akolekar, Ranjit; Wright, Dave; Nicolaides, Kypros H.
Abstract: Objective: To examine the effect of self‐declared race on serum placental growth factor (PlGF) and sFlt‐1/PlGF ratio and the impact on pre‐eclampsia (PE) prediction. Design: Prospective observational study. Setting: Two UK maternity hospitals. Population: 29 035 women with singleton pregnancies attending a routine 35 +0 to 36 +6 weeks' gestation hospital visit, including 654 (2.3%) who subsequently developed PE. Methods: The predictive performance of PlGF and sFlt‐1/PlGF for PE in minority racial groups (versus white) was examined. Main outcome measure: Delivery with PE. Results: Compared with white women, mean PlGF was higher and sFlt‐1/PlGF ratio lower in black, South Asian, East Asian and mixed race women. In white women at a PlGF concentration cut‐off corresponding to a screen‐positive rate (SPR) of 10%, detection rates (DRs) were 49.1% for PE at any time and 72.3% for PE within 2 weeks after screening. In black women, at the same PlGF concentration cut‐off for white women, the SPR was 5.5%, and DRs 33.6% and 55.0%, respectively; the number of PE cases was too small to evaluate screening performance in other racial groups. Using a fixed cut‐off in sFlt‐1/PlGF ratio to identify women at risk of developing PE, similarly diagnostically disadvantaged black women. Bias was overcome by adjusting metabolite concentrations for maternal characteristics and use of the competing risks model to estimate patient‐specific risks. Conclusion: Screening for PE with fixed cut‐offs in PlGF or sFlt‐1/PlGF diagnostically disadvantages black women. It is essential that measured levels of PlGF be adjusted for race as well as other maternal characteristics. Abstract : Linked article : This article is commented on by Philip J. Steer, pp. 88 in this issue. To view this mini commentary visit https://doi.org/10.1111/1471-0528.17305 .